PENGARUH PENAMBAHAN TEPUNG CEKER AYAM RAS TERHADAP DAYA TERIMA DAN KANDUNGAN GIZI MUTIARA TAPIOKA (Tapioca Pearl) - Anna Tirawani Ambarita; Etti Sudaryati; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Tapioca pearl is one of snacks in the form of beverage contents - small and chewy balls that are popular today especially among adolescents. Drinks for tapioca pearls are sweet, where snacks should contain nutrients, especially calcium and protein for growth in adolescence. One source of calcium and protein is chicken claws. Chicken claws can be utilized as flour and serve as an additive in making tapioca pearls. This research type is experiment. The power test receipt uses a complete randomized design study with organoleptic test to see the panelist's preference level against the test food. Panel of power test receipt amounted to 30 people, namely students of the Faculty of Public Health University of North Sumatra. The object of this research is tapioca pearl (tapioca pearl) with chicken starch added 5%, 10%, and 15%. The nutrient content test is done at Food Technology Science Laboratory of University of Sumatera Utara and the content seen include calcium and protein. The result of panelist organoleptic test liked the color, smell, flavor, and texture of tapioca pearls with the addition of chicken 5% chicken flour (A1), while for panelist flavor likes tapioca pearls with 10% (10%) chicken flour added (A2). Based on analysis of Kruskal Wallis test at 5% significant level (<0,05), there were difference of quality two of three treatment on color indicator. The highest nutrient content of protein and calcium is found in tapioca pearls with 15% (A3) chicken ketcher flour. Protein content was measured by Kjeldhal method and Calcium content was measured by permanganometric method. Tapioca pearls with the addition of chicken chicken flour can be an alternative contents of beverages that are high in protein and high in calcium. Further research on the acceptance of tapioca pearls and beverages needs to be done. Keywords: Tapioca Pearl (Tapioca Pearl), chicken claw, The Acceptability, Nutrition Content